An in vitro study of the effects of respiratory circuit setup and parameters on aerosol delivery during mechanical ventilation - Leanne Reilly; Marc Mac Giolla Eain; Sarah Murphy; Andrew O’Sullivan; Mary Joyce; Ronan MacLoughlin; Ronan MacLoughlin; Ronan MacLoughlin (Frontiers in Medicine, 2024)
IntroductionAerosol therapy is often prescribed concurrently during invasive mechanical ventilation (IMV). This study determines the effects of nebuliser position, circuit humidification source, and most importantly, lung health on the delivery of aerosol in simulated adult and paediatric IMV patients. Furthermore, the influence of closed suction catheters on aerosol delivery is also addressed.MethodsA vibrating mesh nebuliser was used to deliver Albuterol to simulated adult and paediatric IMV patients with differing states of lung health. Four different nebuliser positions and two types of humidification were analysed. Closed suction catheter mounts, a mainstay in IMV therapy, were incorporated into the circuits. The mean ± SD dose of aerosol (%) was assayed from a filter at the distal end of the endotracheal tube.ResultsNebuliser placement and circuit humidification source had no effect on the delivered dose (%) in adults, yet both significantly did in the simulated paediatric patients. The use of closed suction catheter mounts significantly reduced the delivered dose (%) in adults but not in paediatric patients. A simulated healthy lung state generated the largest delivered dose (%), irrespective of nebuliser position in the adult. However, different lung health and nebuliser positions yielded higher delivered doses (%) in paediatrics.ConclusionLung health and respiratory circuit composition significantly affect aerosol delivery in both adult and paediatric IMV patients. Nebuliser placement and respiratory circuit humidification source do not affect the delivered dose in adult but do in paediatric IMV patients.